Artemisia selengensis Turcz. leaf extract promotes longevity and stress resistance in Caenorhabditis elegans. (4th March 2022) - Li, Rong; Tao, Mingfang; Xu, Tingting; Huang, Yuting; Zogona, Daniel; Pan, Siyi; Wu, Ting; Xu, Xiaoyun
Abstract: BACKGROUND: Artemisia selengensis Turcz. (AST) is a common edible and medicinal herb possessing extensive biological activities and various health‐promoting functions. However, the anti‐aging effects of AST have been neglected. This work evaluated the effects of AST leaf extract (ASTE) on stress tolerance and longevity in Caenorhabditis elegans . RESULTS: ASTE treatment enhanced stress resistance and significantly extended the lifespan of C. elegans . Moreover, ASTE prolonged the healthspan by increasing body bending and pharyngeal pumping rates, and by reducing the intestinal lipofuscin level and accumulation of intracellular reactive oxygen species (ROS). Caffeoylquinic acids in ASTE, especially dicaffeoylquinic acids, were the major components responsible for these benefits. The mechanism underlying the anti‐aging effect of ASTE occurred by activating insulin/insulin‐like growth factor, SIR‐2.1 signaling and mitochondrial dysfunction pathways, which in turn induced the activity of the transcription factors DAF‐16/FOXO and SKN‐1/Nrf2. CONCLUSION: These findings provide direct evidence for the anti‐aging effects of AST and reveal its potential on promoting healthy aging. © 2022 Society of Chemical Industry.